Theoretical Isotope Generator: An Alternative towards Isotope Pattern Calculator - Kamalrudin, Massila; Stein, Roger D; Sulong, Muhammad Suhaizan; Abdul-Aziz, Azlianor (World Academy of Science, Engineering and Technology, 2007)
A number of mass spectrometry applications are already available as web-based and windows-based systems to calculate isotope pattern and to display the mass spectrum based on the specific molecular formula besides providing necessary information. These applications were evaluated and compared with our new alternative application called Theoretical Isotope Generator (TIG) in terms of its functionality and features provided to prove this new application is working better and performing well. TIG provides extra features than others, complete with several functionality such as drawing, normalizing and zooming the generated graph that convey with the molecular information in a number of formats by providing the details of the calculation and molecules. Thus, any chemist, students, lecturers and researchers from anywhere could use TIG to gain related information on molecules and their relative intensity.